The effect on quality of working life of psychological resilience levels of firefighters. - Tanriverdi, Derya; Özgüç, Safiye (Work, 2026)
Background: Since the firefighting profession requires exposure to high levels of stress and traumatic events, the psychological resilience levels of individuals working in this field are an important factor that directly affects their quality of work life. Objective: This research aims to examine the effects of firefighters' psychological resilience levels on their quality of work life. Method: This study was conducted with a descriptive and correlational design. The sample of the research consisted of 229 firefighters working in the Gaziantep metropolitan municipality department. Research data was obtained through a personal information form, the Connor-Davidson Psychological Resilience Scale, and the Professional Quality of Life Scale. Results: Firefighters' CD-RISC total score is 79.60 ± 15.50, Compassion Satisfaction (CS) total is 39.76 ± 9.09, Burnout levels are 11.73 ± 7.255, and Compassion Fatigue (CF) score average is 14.04 ± 10.29. There is a significant positive relationship between CD-RISC Total and CS (p < 0.001). A significant negative correlation exists between CD-RISC Total score and Burnout (p < 0.001). As a result, it was determined that the model was significant F (1227) = 34.885, P = 0.000, and explained 13% of the variance in the dependent variable (R2 = 0.133). Conclusion: As a result of the research; the psychological endurance and compassion satisfaction of firefighters are high. Their compassion fatigue and burnout levels are low. As the psychological endurance of firefighters increases, compassion satisfaction also increases. As the psychological endurance of firefighters increases, their burnout levels decrease. As compassion satisfaction increases, compassion fatigue decreases. In addition, as compassion fatigue increases, their burnout increases.